Size and dynamics of order-of-entry effects in pharmaceutical markets - Daniel Porath (University of Applied Sciences Mainz, 2016)
There is a wide consensus that the chronological order of firms entering new product markets can affect long-term market shares. Commonly, it is expected that early entrants are able to gain long-lasting competitive advantages over their followers. This is corroborated by a large body of research both on theoretical and empirical grounds, often discussing the conditions under which these so-called order-of-entry effects generally exist or do not exist. Knowledge about existence, size and dynamics of order-of-entry effects is especially important in industries driven by research and development, like pharmaceutical companies aiming at launching innovative, patented drugs. These companies sometimes deliver themselves virtual races for an early launch because they expect substantial advantages from early entrance. The literature on order-of-entry effects for pharmaceuticals indeed confirms advantages for the first mover ("first mover advantage" or "pioneer's advantage"). Apart from this confirmation, however, the existing literature hardly gives any further guideline for companies planning the optimal moment for a new launch. This paper identifies the shortcomings of the existing literature for measuring size and dynamics of order-of-entry effects for pharmaceutical drugs and tries to overcome them. Particularly, this paper advances the literature in the following aspects: First, the size of order-of-entry effects will not be restricted to follow a predefined pattern. Second, the effects will be measured directly in terms of average differences in absolute market shares, and not with proxies or average relative market share differences. This is accomplished by an innovative econometric method. Third, special attention will be given to the question how the order-of-entry effects change over time. This will be done by identifying and then testing the dynamic effects expected by the theoretical literature. Last, but not least, measurement will be carried out with a sample which to the best of the author's knowledge is by far bigger and more representative for the most important pharmaceutical markets than those used in any other publication on the topic.
Keywords: 650; Order-of-Entry Effects; First Mover Advantage; Pharmaceutical Drugs; Fractional Probit Regression; Panel Data